Office Automation: Tools for Alleciating Maual Task and Errors in Document Handling in Federal University of Agriculture, Abeokuta, Ogun State, Nigeria - Boladale Ruth Oluwasina; Adeola Idiat Adepoju; Rasidat Iyabo Olore (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2024)
The issue of manual workload and errors in document management by office managers in an organization heavily relies on the availability of office automation tools as well as the necessary skills and competencies required to use them. This study aims to examine the use of office automation as a tool for reducing manual tasks and errors in document management among office managers at the Federal University of Agriculture, Abeokuta, Ogun State, Nigeria. The study employed a survey design with a population consisting of 100 office managers (secretaries) within the research area. The research instrument was a self-developed and validated questionnaire used to collect relevant data. The collected data were processed using the Statistical Package for Social Sciences (SPSS). Weighted mean and standard deviation were applied to answer the research questions, using an index score of 2.5 as the agreement threshold. The findings revealed that office automation tools are utilized by office managers to alleviate manual tasks and errors in document management. Office automation has a positive impact on reducing manual workload and errors, although office managers face various challenges in its utilization. Based on these findings, it is recommended that prospective office managers undergo adequate training and skills development to ensure effective adoption and utilization of office automation tools. Additionally, business organizations are advised to procure and provide office automation tools to enhance the productivity of their office managers.